SISTEM PENGUKURAN VOLUME MINYAK GORENG BERBASIS IOT - Hafiz Ali (Universitas Lampung, 2026)
Cooking oil is a primary necessity whose volume is often difficult to measure precisely through manual methods, especially in home-industry prototypes. This research aims to design and develop an IoT-based prototype system for measuring cooking oil volume. The system utilizes an ESP32 microcontroller as the main processing unit and an HX711 load cell sensor to detect the mass of the cooking oil. The acquired mass data is subsequently converted into volume units (milliliters) using a density (rho) calculation algorithm based on the average density of cooking oil, which is 0.911 g/ml. The measurement results are displayed in real-time via a web server interface accessible to users through a WiFi network. Based on the test results, the system is capable of measuring cooking oil volume with high accuracy, and the data updates automatically on the web browser. This research is expected to simplify the process of digital and accurate monitoring of liquid volumes.